THE IMPACTS OF HEAVY METALS ON THE GUT MICROBIOME IN COMMON CARP (CYPRINUS CARPIO) (Experimental biology, 2022)
Pollution of freshwaters with heavy metals has become an acute problem in many countries including Kazakhstan, and industrial progress is the primary source of toxic heavy metals. Since gut microbe communities play a significant role in fishes’ homeostasis, immune regulation, metabolism, and disease resistance, it is crucial to understand how heavy metals affect fish's gastrointestinal microbiome diversity. Applications of metagenomics using the 16S rDNA gene's hypervariable regions allow researchers to sequence the gastrointestinal microbiota's genome and identify the diversity of microorganisms, including those that cannot be cultured with traditional microbiological methods. Common carp (Cyprinus carpio) is resistant to highly polluted freshwaters with heavy metals and considered a bioindicator of freshwater pollution. Thus, this paper aims to overview heavy metals' influence on the gastrointestinal microbiome diversity in common carp. Future directions are also discussed to enhance our understanding about the relationships between different environmental factors and gut microbiome diversity of wild fish. Further, it is crucial to understand how each bacterium would help common carp resist heavy metal toxicity.
Keywords: common carp; heavy metal; resistance; gut microbiome; metagenomics